The Development TASC-based Classical Guidance through Work Culture to Enhance Vocational Students' Work Readiness - Ratmi Kuswati; Suwarjo Suwarjo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to develop a classical guidance model based on work culture,